Manusia Silver dan Kebijakan Larangan â€œPengemis Jalananâ€: Anomali Implementasi Peraturan Daerah DIY No. 1 Tahun 2014 di Bantul, Yogyakarta - Bustanul Arifien Rusydi (UIN Sunan Kalijaga Yogyakarta, 2023)
Street begging or panhandler is a social issue that has long existed in Indonesia. The local government has paid attention to handling this social issue in the form of local legal policies (Perda). Even so, this social issue has always been an issue that is difficult for local governments to handle, including enforcement of regulations which often experience deadlock. Why does this impasse happen? This study aims to discuss the prohibition of 'begging' in the Yogyakarta area from a juridical perspective. The data in this study were collected by examining the regulations of 'begging' and supplemented by interviews with the Pol PP Unit (local officer) as the executor of law enforcement of local regulations. This research finds that the norm of 'begging' in the Yogyakarta regulation has an imbalance in legal substance where in the regional regulation 'begging' is defined completely, while the 'giver' is not. In addition to this normative imbalance, the law enforcement of this DIY regional regulation must depend on limited personnel and a sense of 'compassion' in society. This has more or less affected law enforcement for panhandler, especially for the givers, who is giving according to good faith